2013
DOI: 10.1063/1.4816283
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic memristance mechanism of crystalline stoichiometric Ge2Sb2Te5

Abstract: Articles you may be interested inDirect imaging of crystal structure and defects in metastable Ge2Sb2Te5 by quantitative aberration-corrected scanning transmission electron microscopy Appl. Phys. Lett.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 46 publications
4
16
1
Order By: Relevance
“…(4), indicate that the very simple model already offers a very accurate description of the data. The finding of the Nyquist diagram displaying only one semicircle is in striking contrast to literature data, where two semicircles are observed and consequently models comprised of two RC elements are invoked to interpret the data [31,37]. The additional RC element is typically attributed to highly resistive contacts [44] or to highly resistive grain boundaries [31,45,46], where the latter, of course, only makes sense in crystalline systems.…”
Section: B Frequency-dependent Permittivity and Conductivitycontrasting
confidence: 66%
See 1 more Smart Citation
“…(4), indicate that the very simple model already offers a very accurate description of the data. The finding of the Nyquist diagram displaying only one semicircle is in striking contrast to literature data, where two semicircles are observed and consequently models comprised of two RC elements are invoked to interpret the data [31,37]. The additional RC element is typically attributed to highly resistive contacts [44] or to highly resistive grain boundaries [31,45,46], where the latter, of course, only makes sense in crystalline systems.…”
Section: B Frequency-dependent Permittivity and Conductivitycontrasting
confidence: 66%
“…Prokhorov et al [31] and Li et al [37] reported that the resistivity of Ge 2 Sb 2 Te 5 decreases by merely 1 order of magnitude on crystallization. This observation is in conflict with the majority of studies agreeing on a resistivity decrease of about 3-4 orders of magnitude [9,38] when crystallizing PCMs.…”
Section: Published By the American Physical Society Under The Terms Omentioning
confidence: 99%
“…Chua circuit with two diodes and resistors implementing non-linear resistor behavior [8] In order to implement new modified Chua's circuit with GST memristor, the GST memristor's emulator circuit with arXiv:1805.06622v2 [eess.SP] 19 May 2018 3 different levels resistors and two capacitors was constructed because there is no already designed model of GST memristor. As it was suggested by Li et al [9], the emulator circuit consisting of contact resistor of the electrodes R s serially connected to parallel connection of pure resistor and capacitor of GST (R p and C p ). In order to better represent equivalent behavior of the GST memristor two main sources of defect in crystalline grain and at grain boundaries should be considered.…”
Section: Gst Memristor Emulator Circuitmentioning
confidence: 99%
“…Resistive random access memory (RRAM), which achieves data storage through reversible resistance changes in certain dielectrics, is one of the leading candidates for this purpose. Reproducible resistive switching phenomena have been widely observed in oxides [6][7][8][9], chalcogenides [10] and even organic materials [11]. Due to their simple device structure (metal/insulator/metal), high compatibility to standard CMOS flow line and the prospect of 3D integration, certain binary oxides such as Al 2 O 3 [12], HfO 2 [13,14], TiO2 [15,16], and ZrO 2 [17] have attracted more attention.…”
Section: Introductionmentioning
confidence: 99%